PENGARUH PENGGUNAAN DIVINE CIGARETTE TERHADAP LAJU PERTUMBUHAN IKAN BANDENG (Chanos chanos Forskåll, 1775) - Aisa, Aulia; Sunaryo, Sunaryo; Azizah, Ria (977-2407769)
Market demand for milkfish (C. chanos Forskåll, 1775) is continually to increase, since it is used for consumption and live bait for tuna and skipjack. The purpose of this research was to determine the effect of the Divine cigarette fumigation in fish feed on the growth of milkfish (C. chanos Forskåll, 1775). This research used experimental laboratories method with 4 treatments and 3 replications. The first treatment (A) was fumigation the Divine cigarette on fish feed for 5 minutes, the second treatment (B) for 10 minutes, the third treatment (C) for 15 minutes, and the fourth treatment (K) for without fumigation (control). Results of this research showed the highest specific growth rate was obtioned in treatment C which was equal to 2.51% daily. The lowest of mercury content was on the treatment A and C, resulting in decreased levels of mercury in milkfish (C. chanos Forskåll, 1775). Based on the result it can be concluced that the fumigation treatment of Divine cigarette for 15 minutes in fish feed can increased the specific growth rate of the milkfish (C. chanos Forskåll, 1775).